Implementation of Religious Moderation Values in East Priangan Higher Education - Nabhani, Irfan; Ainissyifa, Hilda; Nasrullah, Yufi Mohammad; Fatonah, Nurul (Hanifiya: Jurnal Studi Agama-Agama, 2023)
The notions of extremism and radicalism have penetrated the world of education; Public Higher Education is more vulnerable to radical movements due to the perspective that tends to see religious issues in black and white. Islamic Religious Education (Pendidikan Agama Islam—PAI), taught to students as a primary subject, is an opportunity to shape students' attitudes toward religious moderation as the next generation. East Priangan has a historical burden (heritage) that Indonesia has ever faced; East Priangan is the basis of the Darul Islam Movement, which has the Indonesian Islamic Army (DI/TII) led by SM. Kartosuryo. The study aimed to describe and analyze the implementation of religious moderation values for higher education students in East Priangan, including the University of Garut, the Indonesian Institute of Education, and the Garut Institute of Technology. This study uses a qualitative approach. Data collection techniques using observation, interviews, and documentation. The results showed that the efforts of PAI lecturers in building students' attitudes of religious moderation through understanding the methodology of Islamic teaching, the substance of the PAI curriculum was directed at moderate character, the role models and attitudes of PAI lecturers, there were discussion rooms, Qur’anic learning programs, mentoring and coaching of student activity units, and evaluation. Building a philosophy of religious moderation is an effort for students to respect religious diversity and build student collective awareness at universities in East Priangan.